1,25-Dihydroxyvitamin D inhibits hepatic diacyglycerol accumulation and ameliorates metabolic dysfunction in polycystic ovary syndrome rat models - Yuan, Xin; Yang, Jianshu; Sun, Danlin; Luo, Kaiming; Jiang, Xiaohong; Wang, Long; Xiang, Shoukui; Jiang, Yijie; Ge, Kele; Zhou, Zhiyang; Li, Bowen; Hua, Fei (Frontiers in Pharmacology, 2023)
Purpose: To evaluate influences of 1,25-dihydroxyvitamin D (1,25(OH)2D) on metabolic dysfunction and elucidate the underling mechanism using a polycystic ovary syndrome (PCOS) rat model. Methods: Twenty-four Sprague-Dawley rats have been randomly separated into four groups: control group (CON, 0.5% CMC orally with a dose of 2ml/kg), 1,25VD group (received 0.5% CMC orally and 1,25(OH)2D intraperitoneally, 2.5ug/kg), PCOS group (letrozole orally, 1mg/kg), PCOS+1,25VD group (letrozole orally, 1mg/kg and 1,25(OH)2D intraperitoneally, 2.5ug/kg). The treatments continued for 8 weeks. Body weight, estrus cycle, insulin tolerance test and oral glucose tolerance test of the rats in different groups were assessed. The rats were killed at the 8th weeks, and the plasma, ovarian and liver samples were collected and analyzed. Hepatic lipid profile was characterized by using HPLC/MRM. Results: Letrozole-induced PCOS rats exhibited increased weight, insulin resistance, postprandial glucose abnormalities and dyslipidemia. Compared with the PCOS rats, PCOS+1,25VD rats showed reduced body weight, increased sensitivity to insulin, decreased postprandial glucose and elevated level of high-density lipoprotein cholesterol. Moreover, abnormally increased liver concentrations of total diacyglycerol(DAG) and DAG species of the PCOS rats were reversed by 1,25(OH)2D treatment, and the hepatic DAG and insulin sensitivity was correlated. Conclusions: 1,25(OH)2D inhibits hepatic diacyglycerol accumulation and ameliorates metabolic dysfunction in PCOS rat models.